2021
DOI: 10.1101/2021.07.20.453061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural insight into the stabilization of microtubules by taxanes

Abstract: Paclitaxel (Taxol) is a first-line chemotherapeutic drug that promotes the curved to straight conformational transition of tubulin, an activation step that is necessary for microtubule formation. Crystallization of Taxol bound to tubulin has been long elusive. We found that baccatin III, the core structure of paclitaxel which lacks the C13 side chain, readily co-crystallizes with curved tubulin. Tailor-made taxanes with alternative side chains also co-crystallized, allowing us to investigate their binding mode… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…It is already known that effector-dependent stabilisation and effector-dependent expansion of the microtubule lattice are not necessarily coupled. Prota et al 35 recently showed that baccatin III, a taxol precursor, expands but only marginally stabilises brain GDP-microtubules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is already known that effector-dependent stabilisation and effector-dependent expansion of the microtubule lattice are not necessarily coupled. Prota et al 35 recently showed that baccatin III, a taxol precursor, expands but only marginally stabilises brain GDP-microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work indicates that taxol binds the GDP-tubulin lattice much more tightly than it binds to free tubulin because the polymerisation switch 38 reconfigures the M-loop, which otherwise occludes the taxol site 35 . The lateral contacts made by the M-loops may be the dominant determinant of lattice stability 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work indicates that taxol binds the GDP-tubulin lattice much more tightly than it binds to free tubulin because the polymerisation switch 38 recon gures the M-loop, which otherwise occludes the taxol site 35 . The lateral contacts made by the M-loops may be the dominant determinant of lattice stability 39 .…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that effector-dependent stabilisation and effector-driven expansion of the microtubule lattice are not necessarily coupled. Prota et al 35 recently showed that baccatin III, a taxol precursor, expands but only very marginally stabilises brain GDP-microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules are hollow polymers made of tubulin heterodimers, organised in a 'head to tail' fashion in the microtubule wall 98 . Taxol's core structure, baccatin III, binds to these curved tubulin molecules to elicit its effect 99 . The microtubule cytoskeleton becomes reorganised, forming large bundles.…”
Section: Paclitaxel (Taxol)mentioning
confidence: 99%